362 EFFECT OF INTERNAL AND EXTERNAL ROTATION ON STRAIN IN THE ROTATOR CUFF. (1st January 2005) - Lowry, A.; Oka, R.; Mahar, A.; Pedowitz, R.
Abstract : Purpose: Recurrence of tearing following rotator cuff repairs are thought to result from varying strain within the cuff as the shoulder is moved through different anatomical positions. The purpose of this study was to measure strains in the anterior, midline, and posterior aspects of the rotator cuff tendon under dynamic loading with internal and external rotation. Methods: Two fresh bovine shoulders (16-week old) were dissected, leaving the infraspinatus tendon intact. Shoulders were mounted to a servohydraulic materials testing machine modified to allow internal and external rotation of the humeral head. Three soft tissue strain gages were attached to the tendon at the anterior, middle, and posterior positions. After preconditioning, the tendon underwent cycling loading between 10-100N of tension for 200 cycles. Strain gage data (mm) was recorded at 5Hz for the duration of the test. Testing was repeated at 15 and 30 degrees of both internal and external rotation. (Table ) Conclusion: Assessing the repair sensitivity to its location on the tendon, and hence the loading profile of the tendon, is important in evaluating repair and subsequent treatment. The strain magnitudes seen in the data show dramatically greater strains in the posterior aspect of the tendon when the shoulder is rotated. The directions of strain are partially explained by an artifact of the clamping mechanism utilized. Further investigation is necessary to refine these techniques and further elucidate the relationship between local strain and shoulder position.